Same difference, different sameness: gender-navigating the denominational maze in a Christian African context - Agadjanian, Victor (Religion, state & society, 2024)
The large and growing denominational diversity of sub-Saharan Christianity has attracted considerable scholarly attention, but its implications for individual experiences and well-being remain poorly understood. I examine women’s perceptions, assessments, and practices in everyday construction of church idiosyncrasies, clustering, and hierarchies and women’s abilities and propensities to navigate along and across the corresponding organisational boundaries in a predominantly Christian setting in rural Mozambique. The analysis uses a combination of data from a census of religious congregations, a household survey, in-depth interviews, and participant observation conducted over a decade. It demonstrates that women’s church involvement is socially indispensable yet also subjectively non-binding. Accordingly, church boundaries, while clearly delineated and recognised, are also seen as highly permeable. This permeability facilitates the crossing of those boundaries but may also disincentivise such crossing. Although rural women are increasingly capable of navigating through the religious space, they are generally precluded from exiting that space altogether, as secular options for non-family social anchoring remain very limited in this and other similar low-income patriarchal contexts.